Cognitive self-instruction for classroom processes - Manning, Brenda H., 1946- (State University of New York Press, 1991)
Metacognitive strategies such as cognitive self-instruction have important implications for teaching and learning. Cognitive self-instruction (CSI) has proven successful in improving memory, comprehension, problem-solving, and behavioral self-control of both teachers and students. This book is the first to combine the theoretical/conceptual and research aspects of CSI with applied classroom practices. Drawing on over a decade of research and utilization of the methods described here, Manning suggests applications of CSI for classroom strategies, classroom management, and teacher reflection.